Benet's reader's encyclopedia - Murphy, Bruce, 1962- (New York : Collins, 2008)
Features over 10,000 entries comprising biographies, plot summaries, original and familiar titles, character sketches, historical literary personages, movements, and literary terms.
Keywords: Literature -- Dictionaries; Art -- Dictionaries; Music -- Dictionaries; Art; Literature; Music -- Instruction and study; Dictionaries